13(2x – 1) – 3(9x + 8) = 10 Quick help?

Question

13(2x – 1) – 3(9x + 8) = 10

Quick help?

in progress 0
Jezebel 6 months 2021-08-15T15:30:28+00:00 1 Answers 3 views 0

Answers ( )

    0
    2021-08-15T15:31:44+00:00

    Answer:

    1

    Step-by-step explanation:

    13(2x-1)-3(9x-8) = 10

    or, 26x-13-(27x-24) = 10

    or, 26x-13-27x+21 = 10

    or, 11 – x = 10

    or, 11 – 10 = x

    therefore, x = 1

    I hope it helped

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )